1993
DOI: 10.1002/jbm.820271105
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of poly(ethylene glycol) onto a poly(vinyl alcohol) hydrogel: 2. Evaluation of thrombogenicity

Abstract: Immobilized polyethylene glycol (PEG) reduced the amount of bovine serum albumin (BSA) adsorbed on polyvinyl alcohol (PVA) hydrogel, but did not reduce the platelet reactivity of the hydrogel surface. PEG, molecular weight (MW) 2000 or 5000, with or without a monomethoxy end group, was covalently bound to glutaraldehyde-crosslinked PVA either through a cyclic acetal or an urethane functional group with a surface coverage of 70% (as measured by x-ray photoelectron spectroscopy [XPS]). Immobilization of monometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] There are previous reports that the surface modification of biomaterials with PEG appreciably reduces thrombogenicity. 25,[28][29][30][31][32] Thus, it is widely accepted that PEG shields the cationic surface of biomaterials, reducing their thrombogenicity. 31 In this study, the PEG-b-P[Asp(DET)] micelle system showed no agglomeration even in the presence of blood components including serum albumin (Table 1 and Figure 4), platelets ( Figure 5) and erythrocytes ( Figure 6), whereas BPEI and P[Asp(DET)] polyplexes definitely showed the aggregate formation due to their positively charged character under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, poly(ethylene glycol) (PEG) coating is the most common way to minimize nonspecific fouling of a material surface with biocomponents [4,5], including plasma proteins, and has been performed by a wide variety of methods [6][7][8][9][10][11]. However, most of the PEG-coated surfaces so far reported possess no reactive group on the PEG chain end.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalent use is due largely to its low toxicity and low immunogenicity (1). In addition, due to its protein resistance, it is widely used as a stabilizing surface coating in biological environments (3)(4)(5)(6)(7). For example, PEG-functionalization of liposomes increased their blood circulation times by nearly an order of magnitude (4).…”
mentioning
confidence: 99%
“…For example, PEG-functionalization of liposomes increased their blood circulation times by nearly an order of magnitude (4). In the clinic, ethylene oxide surface grafts are used to reduce protein adsorption onto the surfaces of biomedical polymers (1)(2)(3)(5)(6)(7). This is important for controlling the biological responses to the latter, in part, because protein adsorption is a well established first step in the humoral response against foreign materials (2,8,9).…”
mentioning
confidence: 99%